2014
DOI: 10.1103/physreva.89.023603
|View full text |Cite
|
Sign up to set email alerts
|

Molecular branch of a small highly elongated Fermi gas with an impurity: Full three-dimensional versus effective one-dimensional description

Abstract: We consider an impurity immersed in a small Fermi gas under highly-elongated harmonic confinement. The impurity interacts with the atoms of the Fermi gas through an isotropic short-range potential with three-dimensional free-space s-wave scattering length a 3d . We investigate the energies of the molecular branch, i.e., the energies of the state that corresponds to a gas consisting of a weakly-bound diatomic molecule and "unpaired" atoms, as a function of the s-wave scattering length a 3d and the ratio η betwe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…For the molecular branch, it has been shown theoretically that the strictly one-dimensional energies for the system without tunneling agree quite well with the full three-dimensional energies provided the one-dimensional scattering length a 1D is larger than the harmonic oscillator length a ρ [32]. Correspondingly, we restrict our molecular branch calculations to this regime (i.e., the smallest a 1D considered in Sec.…”
Section: Two-body Hamiltonian and Simulation Of Two-particle Tunnelin...mentioning
confidence: 88%
“…For the molecular branch, it has been shown theoretically that the strictly one-dimensional energies for the system without tunneling agree quite well with the full three-dimensional energies provided the one-dimensional scattering length a 1D is larger than the harmonic oscillator length a ρ [32]. Correspondingly, we restrict our molecular branch calculations to this regime (i.e., the smallest a 1D considered in Sec.…”
Section: Two-body Hamiltonian and Simulation Of Two-particle Tunnelin...mentioning
confidence: 88%
“…Remarkably, also in the latter case strong correlations occur (again, consistent with quasi long-range order) for interaction strengths γ ≫ 1, where multiband effects are important. While previous theoretical studies on confined onedimensional fermions addressed the case of (typically small) harmonic traps [51][52][53][54][55][56][57][58][59][60][61][62][63][64][65], in this Rapid Communication we considered a commensurate periodic potential, using sufficiently large system sizes to inspect the thermodynamic limit. On the one hand, this study provides new unbiased predictions for a paradigmatic model of strongly-correlated Fermi systems, which interpolates between Yang theory of the homogeneous Fermi gas and Lieb-Wu theory of the Hubbard model; on the other hand, it serves as a guide for possible new cold-atoms experiments aiming at observing antiferromagnetism beyond the tight-binding regime [30,66].…”
mentioning
confidence: 99%
“…The experimental progress has generated great interest for few-body problems in one-dimensional geometries for both bosonic [21][22][23][24][25][26][27][28], fermionic [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46], and mixed systems [47][48][49][50][51][52][53][54][55][56][57][58][59][60][61]. Recently, it has been shown that for strong short-range repulsive interactions a 1D two-component Fermi system in a harmonic trap exhibits strong magnetic correlations already at the three-body level [37,40].…”
Section: Introductionmentioning
confidence: 99%